Transportation Services for Older Adults and Preventive Healthcare Attainment - Zeenat Kotval-K; Linda Keilman; Weijing Wang (Urban Science, 2020)
This study examines the impact of the provision of specialized transportation services for older adults on the attainment of preventive healthcare services in selected cities across Michigan. The main hypothesis is that transportation services are critical factors for older adults to not only attain preventive healthcare but also to maintain an active lifestyle that avoids the physical, mental and social isolation that they may face when advised to stop driving. Results indicate that provision of transit services and socio-economic characteristics have statistically significant effects on the attainment of preventive healthcare services. However, although transportation is a critical element for maintaining medical appointments, other factors need to be considered if we truly want to attain better health outcomes for all older adults. Qualitative analyses point to other logistical barriers and the need for more awareness of insurance plans and covered services in order to increase preventive healthcare attainment.